Dermoscopy features on dermatomycosis - Lubis, Flora Marlita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Dermoscopy is a non-invasive tool mainly used to clarify pigmented and nonpigmented skin lesions. Based on its physical properties, dermoscopy is divided into non-polarized and polarized. Dermoscopy examination is a diagnostic technique that is often performed on skin disorders, including skin disorders due to fungal infections. Some of the fungal diseases that are examined bydermoscopy are tinea capitis, pityriasis versicolor and onychomycosis. The dermoscopy features found in tinea capitis are comma hair, corkscrew hair, black dots and short hair. Onychomycosis found dermoscopy chromonychia, white longitudinal stripes and opaque nails (cloudy). The dermoscopy in pityriasis versicolor shows hypopigmented and hyperpigmented patterns.